Impact of COVID-19 on long run and short run financial integration among emerging Asian stock markets - Bhardwaj, Nikhil; Sharma, Nishi; Mavi, Anupreet Kaur (Business, Management and Economics Engineering, 2022)
Purpose –The study aims at exposing any possible impact of COVID-19 on short-run and long-run financial integration among five emerging Asian economies viz., China, South Korea, India, Indonesia and Taiwan.Research methodology – Daily closing indices of selected countries have been analyzed from January 2010 – September 2021. The integration among the selected economies has been examined for long-run and short-run through Johansan co-integration and Granger causality tests respectively.Findings – The analysis revealed that coronavirus weakened integration among nations. The absence of long-run integration was observed after the onset of COVID-19. During pre-covid period, unidirectional as well as bi-directional causal relations were present, but after the outbreak of COVID-19, only South Korea and China reported short-term linkage.Research limitations – The results are subject to the limitation of limited data and reference period. Further, daily returns of different stock markets are subject to domestic shock which has not been analyzed in the present study.Practical implications – Since the absence of integration indicates an ample opportunity for risk minimization through international diversification of the portfolio, the results are expected to be very useful for investors, researchers and regulators.Originality/Value – In present times, researchers are showing keen interest to know the possible impact of COVID-19 on linkages of international financial markets. However in spite of being rapidly growing economies, countries selected in the present study have not been explored much.The present study aims to bridge this research gap.